A survey of solid waste management services in Woldya Town (Ethiopia): Challenges and opportunities for improvement - Aklilu, Teshale; Wodajo, Mengesha Robso; Tasențe, Tănase (Technium Social Sciences Journal, 2021)
In different cities and towns of Ethiopia, solid waste is a major environmental problem. Woldya town also face the challenges of solid waste management. Effective and efficient solid waste management in a town is a mandatory to ensure human and animal health and also to ensure clean and sound able environment in urban development. The aim of this study is to assess challenges and opportunities for improvement of solid waste management services in Woldya town. Interviews, questionnaires and observation were the major tools used for data gathering. The data were analyzed using tables, percentages, pie chart followed by explanation. In Woldya town the residents use illegal methods of solid waste disposal; this includes burning, open dump and ditch. The key challenges of solid waste management services in the town are lack of Awareness, lack of manpower, lack of facilities and financial constraints. The communities recommended that solid waste management can be improved through community participation, increasing funding, create awareness and encourage waste minimization. This study recommends environmental education related to solid waste management plays a great role to promote attitudinal change of the community and strong community participation, improve institutional capacity, strengthen financial capacity, promote private sector participation and preparing disposal site for solid waste